Uma análise da formação continuada oferecida aos professores de Língua Portuguesa que lecionam para os anos finais do Ensino Fundamental da rede Estadual Paulista - Camilo, Camila Neves (2019)
The present research analyzes the continuing education the State of São Paulo Departament of Education provides to its Portuguese Language Teachers in the last years of Primary Education through Diretorias de Ensino- the administrative structure closest to schools. The research object is the regulations, plans and projects of the courses, training modalities with workload of 30 hours, conducted in a five-year period (2012-2017). The method was Content Analysis, by Laurence Bardin. In order to conceptualize teacher preparation, the following authors were used as reference: Carlos Marcelo García, Maurice Tardif, António Nóvoa and Francisco Imbernón, among others. Continuing education has the challenge of dealing with well-known problems in teaching and learning, as well as addressing the gaps brought from undergraduate qualification of teachers. This research sought to identify how these concerns appeared in the continuing education course descriptions and the space dedicated to pedagogical practice in them. The data obtained are presented in figures, graphs and tables. Its results suggest that the teacher preparation is not adequately planned by the State of São Paulo Department of Education and it is not designed to attend demands brought by teachers. On the contrary, external events (large-scale assessments, curriculum changes or essay competitions) are the central motivation for creating the courses